Sugar intake and craving during alcohol withdrawal in alcohol use disorder inpatients. (19th April 2020) - Alarcon, Régis; Tiberghien, Margaux; Trouillet, Raphael; Pelletier, Stéphanie; Luquiens, Amandine; Ahmed, Serge H.; Nalpas, Bertrand; Alaux‐Cantin, Stéphanie; Naassila, Mickaël; Perney, Pascal
Abstract: To assess whether changes in sugar intake and craving occur during alcohol withdrawal in humans, we conducted a prospective, observational study in a university hospital addictions treatment center. Recruited patients had severe alcohol use disorder and were hospitalized for 7 days in the short‐stay unit for alcohol withdrawal and then for 6 weeks in the rehabilitation unit. During the hospital stay, they had no access to alcohol but had full access to sweet products and beverages in a shop and vending machines located inside the hospital. Alcohol craving was assessed using a visual analogue scale on Days 1, 15, and 45. Sugar craving, sweet products stored by patients in their rooms, and weight were assessed on the same days. Thirty‐five patients were included. Sugar craving increased in 14 patients during the hospital stay, whereas no change was observed in the remaining 21. Significant increases in both the amounts of sweet products stored in the patients' rooms ( p < 0.02) and weight ( p < 0.05) were observed only in the sugar craving group. During the same period, alcohol craving decreased significantly in all patients. Changes in tobacco smoking were not different according to the sugar craving status and therefore cannot explain the observed differences. In conclusion, increased intake and craving for sugar after alcohol withdrawal were observed in 40% of the patients included in our prospective study, and these results were similar to those of a study conducted in the alcohol post‐dependent state model in rats. Abstract : We assess whether changes in sugar intake and craving occur during alcohol withdrawal in 35 inpatients. Alcohol craving, sugar craving, sweet products stored by patients in their rooms, and weight were assessed on Days 1, 15, and 45. Sugar craving increased in 14 patients (40%). Significant increases in both the amounts of sweet products stored and weight were observed only in the group with increased sugar craving. Changes in tobacco smoking were not different according to the sugar craving status.